Informed consent in anesthesiology: an exploratory study - Fontes, Bárbara; Marina, Sílvia; Andrade, Diana; Dias, Sofia; Ricou, Miguel (Acta Bioethica, 2022)
In the literature Informed consent (IC) assumptions is well established. However, the different stages and the conditions under which the IC for anesthetic practices is obtained, is scarce. The aim of the present study is to explore the phases and conditions of IC in anesthesiology. Anonymized clinical records of 325 patients submitted to anesthetic procedures at the Institute of Oncology of Porto were analyzed. A total agreement between the anesthetic techniques established in the IC and those performed, was reach with 270 patients. The importance of IC in clinical practice is discussed and an ideal process for IC is argued.